Thank you for smoking : fun and fearless recipes cooked with a whiff of wood fire on your grill or smoker - Disbrowe, Paula (Ten Speed Press, 2019)
"Featuring an impressive array of smoke-infused recipes that extend well beyond the realm of rib joints, Thank You for Smoking shows home cooks how easy it is to rig a gas or charcoal grill or use a backyard smoker to infuse everything you love to eat--from veggies and greens to meat and fish--with a smoky nuance"--